2016
DOI: 10.1057/jors.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy prediction of small and medium enterprises using a flexible binary generalized extreme value model

Abstract: We introduce a binary regression accounting-based model for bankruptcy prediction of Small and Medium Enterprises (SMEs). The main advantage of the model lies in its predictive performance in identifying defaulted SMEs. Another advantage, which is especially relevant for banks, is that the relationship between the accounting character-istics of SMEs and response is not assumed a priori (e.g., linear, quadratic or cubic) and can be determined from the data. The proposed approach uses the quantile function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 59 publications
(84 reference statements)
3
62
0
7
Order By: Relevance
“…In Refs. and extreme values models (generalized extreme value (GEV) and generalized extreme value additive (BGEVA)) to predict default of a sample of Italian SMEs was extended, and in Ref. the performance of U.K. and Italian small firms was compared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Refs. and extreme values models (generalized extreme value (GEV) and generalized extreme value additive (BGEVA)) to predict default of a sample of Italian SMEs was extended, and in Ref. the performance of U.K. and Italian small firms was compared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Calabrese and Osmetti (2015) propose the BGEVA model by including an additive component to the GEV model. The BGEVA model has been then improved by Calabrese, Marra, and Osmetti (2016) . Several studies ( Andreeva et al, 2016;Calabrese et al, 2016;Calabrese & Osmetti, 2013;2015 ) have shown that the GEV model outperforms the logistic and the probit models even if the percentage of ones in the sample is one per cent.…”
Section: Gev Modelmentioning
confidence: 99%
“…As a result, an accurate FDSS risk assessment that distinguishes nondefault (healthy) entities from the default (bankrupt) ones can fruitfully assist to avoid financial scandal and crisis (Calabrese, Marra, & Silvia, 2016). Financial crisis mostly stemmed from the credit default of individual client together with the corporate bankruptcy.…”
Section: Introductionmentioning
confidence: 99%
“…If vigilant attention is paid to the relevant studies (see,e.g., Section 2), however, one can observe the lack of topological applications of MLPs and SVMs, that is, in most cases when using MLP algorithms, nothing is stated about activation functions (AFs) on one side, being used only one HL on the other side; lots of previous evidence have consistently demonstrated that escalating the number of HLs and experimentations with AFs make the MLP network more commanding and generate the more feasible outcome (Jeong, Min, & Kim, 2012;Luo et al, 2017). Furthermore, their databases for experiential investigations were to some extent imperfect, that is, research findings regarding FDSSs with "purely bankruptcy databases" are much more scarce, even though the size of corporate lending makes sound lending decisions, which is a matter of national interest (Calabrese et al, 2016). Xu, Tang, & Li, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation